PENERAPAN METODE BERCERITA DALAM MENINGKATKAN KETERAMPILAN MENCERITAKAN KEMBALI ISI FABEL PADA SISWA KELAS VII SMP - Eka Putri Vania; Moh. Ahsan Shohifur Rizal; Kholik (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2023)
ABSTRACT The purpose of this study is to describe the application of storytelling techniques in improving students' skills in retelling moral stories, especially fables. The research method used is a qualitative descriptive approach involving 12 grade VII students of SMP PGRI AS Sarqowi. Data collection was carried out through interviews, information recording, and documentation as data sources. The results showed that the application of storytelling techniques was effective in increasing students' skills in explaining the contents of fables, being able to convey the orientation, complications, resolution and code of fable. From this study it can be concluded that the use of storytelling techniques is effective in increasing students' understanding of structure and communication in fables.